The role of external fixation in the management of infected avascular necrosis after traumatic talus fractures. (September 2020) - Engelmann, E.W.M.; Wijers, O.; Posthuma, J.; Schepers, T.
Abstract: Purpose: Avascular necrosis (AVN) after fractures of the talus is a distinct and challenging clinical entity that is associated with poor outcomes. Although several articles are published on the management of posttraumatic AVN of the talus, very little is known about the management of infected AVN after talus fractures. Therefore, three cases of infected AVN were treated successfully by extensive debridement, external fixation and arthrodesis. Methods: Three cases of infected AVN of the talus were encountered after a mean of 3 months (range 2–6 months) after initial reconstructive surgery. Suspected infection was confirmed by positron emission tomography scan (PET-CT). Management involved extensive debridement, PMMA cement if necessary and final fusion using medial external fixator, accompanied by culture guided antibiotics. Functional outcome was assessed using the Foot Function Index (FFI) and the American Orthopaedic Foot and Ankle Society hindfoot score (AOFAS). Quality of life (QOL) was measured by the EuroQol-5D (EQ-5D). Results: After a mean follow up of 24 months (range 13–29), FFI index scores ranged from poor to good (23, 50, 56) with similar AOFAS scores indicating poor to fair functional outcome (38, 41, 71). The EQ-5D score was 0.78. Overall patient satisfaction was high with a mean VAS of 8.3 (range 8–9). Conclusion: Infected talar AVN is a rare condition associated with severe long-term morbidity in term of joint function. The authors recommend extensive debridement and arthrodesis by means of external fixation, followed by post-operative culture-guided antibiotics for the treatment of infected avascular necrosis of traumatic talar fractures. Shared decision-making and expectation management are of crucial importance and may lead to high patient satisfaction despite low functional outcomes. Level of evidence: IV, Retrospective case series.